Do Interpersonal Conflict, Aggression and Bullying at the Workplace Overlap? A Latent Class Modeling Approach - Notelaers, Guy; Van der Heijden, Beatrice; Guenter, Hannes; Nielsen, Morten Birkeland; Einarsen, Ståle Valvetne (Frontiers in Psychology, 2018)
In this paper, we tackle an important but unresolved research question: How distinct are workplace conflict, aggression and bullying? We study this question by means of latent class (LC) analysis using cross-industry data from 6,175 Belgian workers. We find a two-factor solution (conflict-aggression versus bullying) to provide the best fit to the data. Employees with low exposure to conflict-aggression and bullying perceived the phenomena as mostly overlapping. Employees who were exposed more frequently to the phenomena reported them to be more distinct - especially so for workplace bullying. We also find conflict-aggression and bullying to have distinct relationships with well-being and strain outcomes. These findings entail that a simple unifying approach or a single label for all three phenomena is not appropriate, at least from a measurement point of view and from the perspective of those exposed. Our results have important implications for the theoretical understanding of conflict, aggression and bullying, and for practitioners who provide support to affected employees including policymakers who help prevent and manage these problems at the workplace.